Extended x-ray absorption fine structure of copper in cytochrome c oxidase: Direct evidence for copper—sulfur ligation - Scott, Robert A. (1981)
The copper x-ray fluorescence excitation spectrum of cytochrome c oxidase (ferrocytochrome c:oxygen oxidoreductase, EC 1.9.3.1) has been recorded in the 245—270 K range. The beat pattern observed in the extended x-ray absorption fine structure can be accounted for only by postulating a combination of sulfur and nitrogen (or oxygen) ligands to the copper. The average Cu—S distance is 2.27 ± 0.02 Å and the average Cu—N (or Cu—O) distance is 1.97 ± 0.02 Å. The amplitudes require ca, 1-1.5 sulfurs and 2 nitrogens (or oxygens) per copper. The distribution of sulfur ligands between Cu(A) and Cu(B) sites is not known, although there is some evidence that two sulfur atoms are bound to Cu(A).